Prognostic Nutritional Index and Oxygen Therapy Requirement Associated With Longer Hospital Length of Stay in Patients With Moderate to Severe COVID-19: Multicenter Prospective Cohort Analyses - Fernandes, Alan L.; Reis, Bruna Z.; Murai, Igor H.; Pereira, Rosa M. R. (Frontiers in Nutrition, 2022)
To evaluate whether the prognostic nutritional index (PNI) is related to oxygen therapy requirement at hospital admission and to ascertain the prognostic effect of the PNI and the oxygen therapy requirement as predictors of hospital length of stay in patients with moderate to severe coronavirus disease 2019 (COVID-19). This is a post-hoc analysis in hospitalized patients with moderate to severe COVID-19. The participants were categorized into non-oxygen therapy (moderate COVID-19 not requiring oxygen therapy), nasal cannula therapy (severe COVID-19 requiring nasal cannula oxygen therapy), and high-flow therapy (severe COVID-19 requiring high-flow oxygen therapy). PNI was calculated for each patient according to serum albumin and total lymphocyte count. The participants were categorized into malnutrition, mild malnutrition, and non-malnutrition. According to PNI, malnutrition was more prevalent in the high-flow therapy group with significant lower PNI compared to both groups even after adjusting for the center and C-reactive protein. Patients in the high-flow therapy group and malnutrition status showed a significant longer hospital length of stay compared to their counterparts. The multivariable Cox proportional hazard models showed significant associations between both oxygen therapy requirement and PNI categories and hospital discharge. In addition to oxygen therapy requirement, the low PNI was associated with longer hospital length of stay. Our findings suggest that PNI could be useful in the assessment of nutritional status related to the prognosis of patients with moderate to severe COVID-19